2016
DOI: 10.2489/jswc.71.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient management planners' feedback on New York and Pennsylvania phosphorus indices

Abstract: State phosphorus indices (PIs) are being evaluated across the United States due to variability in phosphorus (P) management recommendations and questions about the lack of water quality improvement in some watersheds. Nutrient management planners in New York (NY) and Pennsylvania (PA) were surveyed via two separate "but related" questionnaires to document perspectives on the current NY-PI and PA-PI and to obtain recommendations for improvements. Many planners were content with the current versions of the PIs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 2 publications
2
23
1
Order By: Relevance
“…The feedback from the planners indicated a high ranking for relevance of all transport P factors in the initial NY‐PI. They did, however, suggest that a new NY‐PI could more strongly discourage manure application during winter and to fields near streams and could more strongly promote manure incorporation or injection, establishment of cover crops, maintenance of ground cover with crop residues, and implementation of setbacks within production fields and vegetated buffers outside of fields (Cela et al, 2016). This feedback was consistent with findings that the NY‐PI allows for relatively high manure application rates when STP is low, even if the risk of transport of the manure to streams is high.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The feedback from the planners indicated a high ranking for relevance of all transport P factors in the initial NY‐PI. They did, however, suggest that a new NY‐PI could more strongly discourage manure application during winter and to fields near streams and could more strongly promote manure incorporation or injection, establishment of cover crops, maintenance of ground cover with crop residues, and implementation of setbacks within production fields and vegetated buffers outside of fields (Cela et al, 2016). This feedback was consistent with findings that the NY‐PI allows for relatively high manure application rates when STP is low, even if the risk of transport of the manure to streams is high.…”
Section: Resultsmentioning
confidence: 99%
“…Building on the importance of a stakeholder‐driven process already employed with the development of the initial NY‐PI, a second survey was developed to specifically request feedback on the NY‐PI, while a very similar survey was conducted in Pennsylvania with focus on the Pennsylvania PI (Weld et al, 2007) to enable comparisons across state boundaries. These surveys, conducted in 2014 to 2015, showed that the current versions of each PI were well accepted in their respective states, documented the type of management practices that planners experienced as high risk, and identified overreliance on STP as an issue in high‐risk scenarios (Cela et al, 2016). Lessons learned from the survey were used to guide development of a new NY‐PI approach and to identify transport factors and BMPs to be included in the new NY‐PI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The emergence of dissolved P in watersheds such as the Conestoga (Fig 1; Table 1) reflects an array of recalcitrant sources of P, exacerbated by increased infrastructure needs of small livestock operations (Kleinman et al, 2012). Although conservation tillage is widespread in the region (roughly two‐thirds of the Bay watershed's farm soils are in no‐till or some type of perennial forage), adoption of cover crops in Pennsylvania is not as extensive as in Maryland, where it has been heavily subsidized (13 vs. 29% of cropland area in Pennsylvania and Maryland, respectively, in 2017), and soil erosion remains a dominant concern of nutrient management specialists and resource conservation programs (Cela et al, 2016; Bryant, 2019). Even so, the emergence of dissolved P as a concern may also reflect the success of soil conservation programs, which struggle to deal with the persistent issue of vertical soil P stratification (Baker et al, 2017).…”
Section: Southeastern Pennsylvaniamentioning
confidence: 99%